CONCERNING THE CYCLIC NATURE OF CRISES - Irina N. Nazarova (Вестник Российского экономического университета имени Г. В. Плеханова)
At present we can observe the finance and economic crisis which happened in global scale. The article provides the notion of crisis, describes its principle characteristics and discloses the cyclic nature of crises. It is pointed out that crisis is one-two phases of the wave economic cycle. Different degree of economic disproportions is a result of economic wave lowering which corresponds to crisis. The author investigates the achievements of the cyclic theory and advantages that it provides for economic situation analysis, especially in conditions of the crisis. Undeveloped aspects of economic cycles are shown and their importance for analysis and prevention of deep sinking in crisis are illustrated.